2012
DOI: 10.5688/ajpe76471
|View full text |Cite
|
Sign up to set email alerts
|

An Interprofessional Course Using Human Patient Simulation to Teach Patient Safety and Teamwork Skills

Abstract: Objectives. To assess the effectiveness of human patient simulation to teach patient safety, teambuilding skills, and the value of interprofessional collaboration to pharmacy students. Design. Five scenarios simulating semi-urgent situations that required interprofessional collaboration were developed. Groups of 10 to 12 health professions students that included 1 to 2 pharmacy students evaluated patients while addressing patient safety hazards. Assessment. Pharmacy students' scores on 8 of 30 items on a post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 15 publications
(11 reference statements)
0
70
0
1
Order By: Relevance
“…7,11,15,17,18,20,27 There appeared to be no published evidence on ideal simulation group size, but in the present study, it was important to determine the maximum group size with which students felt comfortable. Determining that a group size of 8 to 9 students was acceptable to students was a valuable finding in this study, as large class sizes make it prohibitive to have smaller simulation group sizes, if facilitator and "patient" fatigue are to be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…7,11,15,17,18,20,27 There appeared to be no published evidence on ideal simulation group size, but in the present study, it was important to determine the maximum group size with which students felt comfortable. Determining that a group size of 8 to 9 students was acceptable to students was a valuable finding in this study, as large class sizes make it prohibitive to have smaller simulation group sizes, if facilitator and "patient" fatigue are to be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Our study design addressed the need outlined in the Garling Report (Garling 2008) to provide these clients with effective holistic client centred care by deliberately developing eight simulation scenarios selected from actual cases of social care clients with complex chronic conditions. More specifically, our project combined IPE with scenario-based education (SBE) and as such our results might be more closely compared with more recent studies of IPE programs developed by HEPS which have similarly utilised SBE to deliver IPE programs for undergraduates (Shrader et al 2013, Kyrkjebo et al 2006, Vyas et al 2012, Wamsley et al 2012, and Kilminster et al 2004. Our study was different in respect of the use of volunteer SCs, the rural setting in community health, and the pairing of different disciplines to collaborate in a simulated intake interview.…”
Section: Discussionmentioning
confidence: 73%
“…Recent reports of combined IPE/simulation team training using high fidelity mannequins (Shrader et al 2013), standardised patients (Wamsley et al 2012), or hybrid simulations (Shrader et al 2013, Kilminster et al 2004, and Vyas et al 2012 suggest outcomes include improved understanding of roles of other professionals and increased awareness of the importance of interprofessional communication for patient safety. Further, Shrader et al (2013) found that effective interprofessional teamwork is associated with positive clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Los autores de los art铆culos seleccionados consideran relevantes para la seguridad del paciente los siguientes factores: desarrollo de habilidades de comunicaci贸n, colaboraci贸n interprofesional 7,8 , gesti贸n en situaciones de emergencias 4,9,10 y confianza en los conocimientos adquiridos. Estas competencias se favorecen con el uso de la simulaci贸n 11 , aumentando la conciencia del error y su valor pedag贸gico 12,13 .…”
Section: Discussionunclassified